ADOPSI TEKNIK TANAM JAJAR LEGOWO DALAM MENDUKUNG AGRIBINIS PADI SAWAH DI PROVINSI RIAU - Rizqi Sari Anggraini; Febri Febri; Jakoni Jakoni (UIR Press, 2015)
Parallel technique of legowo was disseminated to SLPTT locations in Riau Province for 9 regencies, i.e., Indragiri Hilir (25 LL), Indragiri Hulu (60 LL), Rokan Hulu (182 LL), Pelalawan (50 LL), Rokan Hilir (25 LL), Kuantan singingi (63 LL), Kampar (140 LL) and Siak (33 LL). However, the research related to affectivity of parallel technique of legowo for supporting the increase of rice production in Riau Province has not been conducted. Therefore, it is needed a research on adoption of parallel technique of legowo. The purpose of this research was to increase knowledge, attitude, and skill of farmers in activity for optimally using inputs by parallel technique of legowo planting. The results showed that production cost per growing season of rice farming for cooperator farmer was higher than non-cooperator, namely Rp. 9,247,711.63/ha and Rp. 8,815,445.83/ha, respectively. The high cost incurred by cooperator farmer was due to the high use of fertilizer.